Studying the Over-Time Construction of Knowledge in Educational Settings: A Microethnographic Discourse Analysis Approach. Issue 1 (March 2020) - Green, Judith L.; Baker, W. Douglas; Chian, Monaliza Maximo; Vanderhoof, Carmen; Hooper, LeeAnna; Kelly, Gregory J.; Skukauskaite, Audra; Kalainoff, Melinda Z.
This review presents theoretical underpinnings supporting microethnographic-discourse analytic (ME/DA) approaches to studying educational phenomena. The review is presented in two parts. Part 1 provides an analytic review of two seminal reviews of literature that frame theoretical and methodological developments of microethnography and functions language in classrooms with diverse learners. Part 2 presents two telling case studies that illustrate the logic-of-inquiry of (ME/DA) approaches. These telling case studies make transparent how theoretical considerations of cultural perspectives on education inform decisions regarding research methodology. Telling Case Study 1 makes transparent the logic-of-inquiry undertaken to illustrate how microanalyses of discourse and action among participants in a physics class provided an empirical grounding for identifying how different groups undertook a common task. This case study shows how ethnographically informed discourse analyses formed a foundation to theoretically identify social processes of knowledge construction. Telling Case Study 2 makes transparent multiple levels of analysis undertaken to examine ways that creative processes of interpretation of art were communicated and taken up in an art studio class across multiple cycles of activity. Taken together, these telling case studies provide evidence of how ME/DA provides a theoretically grounded logic-of-inquiry for investigating complex learning processes in different educational contexts.